2020
DOI: 10.1111/jai.14033
|View full text |Cite
|
Sign up to set email alerts
|

Increasing temperature associated with increasing grilse proportion and smaller grilse size of Atlantic salmon

Abstract: Effects of temperature on Atlantic salmon (Salmo salar) were analysed using Carlin tag recovery data (1985–2014), and mixed‐stock catch data (smolt years from 2001 to 2012) in northern parts of the Baltic Sea. During warmer summers, the mean smolt length of the recaptured salmon tended to be smaller, and salmon were recaptured more frequently in feeding grounds closer to the home rivers in the Gulf of Bothnia, while colder summers were associated with more recaptures further south, in the Baltic Main Basin. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…This has been described from elsewhere in Scotland (Youngson et al, 2002) and there is evidence of this occurring in Loch Lomond (see below). A similar pattern has also been identified in several Finnish salmon populations in the Baltic Sea area; Kallio-Nyberg and colleagues (Kallio-Nyberg et al, 2020) found that a higher proportion of the population returned as 1SW salmon between 2001 and 2012 and this was significantly correlated with increasing temperature in the area. The same study also found that even within the 1SW fish, body size decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 75%
“…This has been described from elsewhere in Scotland (Youngson et al, 2002) and there is evidence of this occurring in Loch Lomond (see below). A similar pattern has also been identified in several Finnish salmon populations in the Baltic Sea area; Kallio-Nyberg and colleagues (Kallio-Nyberg et al, 2020) found that a higher proportion of the population returned as 1SW salmon between 2001 and 2012 and this was significantly correlated with increasing temperature in the area. The same study also found that even within the 1SW fish, body size decreased with increasing temperature.…”
Section: Discussionsupporting
confidence: 75%
“…Temperature may also influence where in the ocean the salmon feed. During warmer summers, Atlantic salmon in the Baltic Sea fed closer to their home river in the Gulf of Bothnia, while in colder summers, they fed farther south in the Baltic Main Basin [172]. Furthermore, the temperature influences the timing of the return migration.…”
Section: Behavioural Traitsmentioning
confidence: 99%
“…The abundance of adult Atlantic salmon, Salmo salar Linnaeus, 1758, returning to rivers around the North Atlantic Ocean has been closely watched since humans began to exploit the resource (Dunfield 1985;Mills 1989). Historically, salmon populations were so abundant writers related that fish nearly overflowed onto the riverbanks (Bigelow and Schroeder 1953;Hindar et al 2007;Nyberg-Kallio et al 2020). On the other hand, there have always been periods of scarcity (Huntsman 1931a;George 1982).…”
Section: Introductionmentioning
confidence: 99%